144 Qualitative component of a longitudinal, mixed methods programme evaluation using in-depth interviews. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Johnston, Bridget; Mathews, Gillian; Patterson, Anne; Bravington, Alison; Hardy, Beth; Seymour, Jane
Abstract : Background: Macmillan Specialist Care at Home seeks to enhance patient-centred care through community and home-based palliative and end of life care services. This article reports a qualitative study that formed part of a larger evaluation of a multi-site implementation of the specialist palliative care community service. Aim: To examine caregiver, patient and carer experiences of service implementation and identify how its key features: early referral; clinical interventions at home; avoiding hospital admissions; and facilitating patients to die in their preferred place of death, worked in practice. Methods: Qualitative component of a longitudinal, mixed methods programme evaluation using in-depth interviews (n=49 [Health professionals (n=18), volunteers (n=14), patients (n=9) and lay carers (n=8) from six community-based sites]) supported by a visual research method 'Pictor' to facilitate dialogue about experiences of care. The data were analysed using thematic analysis. Results: Effective partnerships between generalist and specialist teams improve the overall quality of community and home-based palliative and end of life care. The collaborative approach instils confidence and empowers patients and carers, principal factors in crises-prevention and enabling home deaths. Key themes were: Early referral and rapport; Benefits of seamless care. Averting crises situations; Community consultant as catalyst; Home-based clinical interventions Attending to wider aspects of care; Managing expectations through patient and carer education. Conclusions: Macmillan Specialist Care at Home is a complimentary resource for community-based palliative and end of life care that can extend and greatly enhance the quality of care experience for people with life limiting illnesses and their families. Joint education, training and continuing professional development for specialist teams and existing community staff is advocated to promote shared knowledge and to forge and strengthen bonds between specialist and generalist health and social care professionals. Further testing of the mechanisms involved in implementation will improve transferability potential.